"From Bones to Years: Unlocking Age through Ossification Secrets” - Dr.Minal Bhatia; Dr Jasbir Singh; Dr Raman Sharma; Dr Vipin Koushal (International Journal of Medical Toxicology and Legal Medicine, 2025)
Age assessment in forensic sciences is crucial for identifying unidentified remains and addressing legal issues, particularly in cases of crimes, civil cases and mass tragedies. Thisneed for age estimation of living individuals has also increased significantly in recent decades due to various civil and criminal cases as well asglobal migration trends which influence legal outcomes. This case study examines a unique scenario involving a female petitioner asserting she is over 18 years old, while her parents claim she is only 14, seeking to annulate her marriage under the Prohibition of Child Marriage Act, 2006. This case illustrates the vital role of modern forensic medicine in age estimation in legal contexts and underscores the ethical and legal implications of age determination in resolving disputes surrounding age, identity and marital status.